Diagnóstico técnico-económico e plano de ação para o setor de rochas ornamentais no estado do Rio de Janeiro - Margueron, Claudio; Coelho, Cristiane Mendes (Anuário do Instituto de Geociências, 1997)
This article initially undertakes a diagnostic study of the Marble and Granite Industry in Brazil and in Rio de Janeiro State. It shows the main uses for marble and granite and describes the key problems faced by this mining-mineral bencficiation sector in Brazil and Rio de Janeiro: production, institutional, roads and ports infrastructure, low value of exports, Italian Cartel, knowledge of distribution channels, market requirements and technology. It also describes in detail the geographic location, reserves and production of marble and granite in the state of Rio de Janeiro and the export-import situation for Brazil and for Rio de Janeiro State. Finally in its conclusions this article presents an ACTION PLAN for the Marble and Granite Sector of the state of Rio dc Janeiro economy.